TREE SPECIES DIVERSITY AND SOIL MACROFAUNA IN RELATION TO SOIL PHYSICOCHEMICAL PROPERTIES IN FOREST RESERVE AND DISTURBED SITE OF MALADUMBA, BAUCHI STATE, NIGERIA - Sani, Mohammed; Kaseem, Salami D.; Muhammed, Suleiman I.; Mohammad, Mahmud; Mamman, Jabiru; Yusuf, Shehu (FUDMA JOURNAL OF SCIENCES, 2026)
Human disturbance is one of the major threats to Maladumba Forest Reserve. Assessing tree species and macro soil fauna diversity associated with soil properties in protected and disturbed sites can inform sustainable management for conserving biodiversity and ecosystem functions in tropical forest. Woody plants with a diameter at breast height of ≥10 cm were identified, recorded; the tree basal area were calculated. Soil samples were collected using a soil auger at 1-15 cm depth during the peak rainy season in 2024 for examined physical and chemical properties. Soil macro fauna was identified, counted and recorded based on morphological characteristics. Shannon Diversity Index was used to calculate the Soil Macro fauna while T. Test was employed to compare soil properties between sites, and correlation analysis to determine relationships between the soil properties and tree species distribution and soil macro fauna diversity. A total of 53 individuals (13 families) and 12 individuals (12 families) tree species were recorded from the protected and disturbed sites respectively. Tree diversity was higher in the protected area (3.93) compared to the disturbed site (1.63), with the highest tree distribution (41.51%) found in the 81cm and above. Soil macrofauna counts were 282 (11 families) in the protected and 202 (11 families) in the disturbed sites while Soil macrofauna diversity was 2.60 and 1.32 respectively. Soil pH and aluminum showed significance across sites, while the dominant soil type in both are sandy loam. Protected sites showed higher tree diversity and soil macrofauna diversity compared to disturbed sites.